Assessing auditory evoked potentials of wild harbor porpoises (Phocoena phocoena) - Ruser, A.; Dähne, M.; Van Neer, A.; Lucke, Klaus; Sundermeyer, J.; Siebert, U.; Houser, D.; Finneran, J.; Everaarts, E.; Meerbeek, J.; Dietz, R.; Sveegaard, S.; et al. (Acoustical Society of America, 2016)
© 2016 Acoustical Society of America. Testing the hearing abilities of marine mammals under water is a challenging task. Sample sizes are usually low, thus limiting the ability to generalize findings of susceptibility towards noise influences. A method to measure harbor porpoise hearing thresholds in situ in outdoor conditions using auditory steady state responses of the brainstem was developed and tested. The method was used on 15 live-stranded animals from the North Sea during rehabilitation, shortly before release into the wild, and on 12 wild animals incidentally caught in pound nets in Denmark (inner Danish waters). Results indicated that although the variability between individuals is wide, the shape of the hearing curve is generally similar to previously published results from behavioral trials. Using 10-kHz frequency intervals between 10 and 160 kHz, best hearing was found between 120 and 130 kHz. Additional testing using one-third octave frequency intervals (from 16 to 160 kHz) allowed for a much faster hearing assessment, but eliminated the fine scale threshold characteristics. For further investigations, the method will be used to better understand the factors influencing sensitivity differences across individuals and to establish population-level parameters describing hearing abilities of harbor porpoises.